PENGENALAN DAN IMPLEMENTASI UI/UX DAN PEMROGRAMAN WEB DASAR PADA SISWA SEKOLAH MENENGAH PERTAMA (Studi Kasus: SMPN 3 PAGEDANGAN) - Agus Rahmawan; Alva Herbart Miftahul Firdaus; Dimas Adiansyah; Fauzan Kholid; Maulana Sandy; Mochamad Masdarul Anwar; Muhammad Bintang; Rafi Ivan Alessandro; Samsul Maarif; Syech; Galuh Saputri (Abdi Jurnal Publikasi, 2024)
Community service is an integral part of the Tridharma of Higher Education, aimed at making a tangible contribution to society. This activity was carried out at SMPN 3 Pagedangan under the theme